2005
DOI: 10.1002/jbt.20088
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte antioxidant defense response against cigarette smoking in humans—the glutathione S‐transferase vulnerability

Abstract: Cigarette smoking leads to uptake of a multitude of reactive chemicals including many electrophiles and may also give rise to oxidative stress. Human red blood cells are important targets for electrophilic and oxidant foreign compounds. We investigated the oxidative stress in erythrocytes upon cigarette smoking, and the response of antioxidant defense system against it. With this aim, simultaneous determination of erythrocyte superoxide dismutase (SOD), selenium dependent glutathione peroxidase (Se-GPx), catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 33 publications
5
30
2
2
Order By: Relevance
“…Guentsch et al (23) and Akalın et al (24) reported that MDA levels increased in the saliva of smokers versus nonsmokers and these findings were in concordance with those reported by some previous studies in venous blood erythrocyte/serum/plasma (22,(25)(26)(27). Our findings support these results.…”
Section: Discussionsupporting
confidence: 93%
“…Guentsch et al (23) and Akalın et al (24) reported that MDA levels increased in the saliva of smokers versus nonsmokers and these findings were in concordance with those reported by some previous studies in venous blood erythrocyte/serum/plasma (22,(25)(26)(27). Our findings support these results.…”
Section: Discussionsupporting
confidence: 93%
“…Among the present controls, catalase activity was significantly higher in ex-smokers than in current smokers. Although healthy smoking controls may also be subjected to oxidative stress, they do not have COPD and might not exhibit the compensatory increase in erythrocyte catalase activity, which is supported by previous reports [27,28].…”
Section: Discussionsupporting
confidence: 80%
“…Hence it is suggested that there may be a strong association of GST with lung function at the molecular level [44][45][46][47][48]. Interestingly, in this investigation, we also found GST activity was not only lower in COPD but also progressively decreased with the severity of COPD disease.…”
Section: Discussionsupporting
confidence: 67%